Lung cancer nanomedicine: potentials and pitfalls. (November 2015) - Bölükbas, Deniz Ali; Meiners, Silke
Lung cancer is by far the most common cause of cancer-related deaths in the world. Nanoparticle-based therapies enable targeted drug delivery for lung cancer treatment with increased therapeutic efficiency and reduced systemic toxicity. At the same time, nanomedicine has the potential for multimodal treatment of lung cancer that may involve 'all-in-one' targeting of several tumor-associated cell types in a timely and spatially controlled manner. Therapeutic approaches, however, are hampered by a translational gap between basic scientists, clinicians and pharma industry due to suboptimal animal models and difficulties in scale-up production of nanoagents. This calls for a disease-centered approach with interdisciplinary basic and clinical research teams with the support of pharma industries.